Pengaruh Struktur Modal, Profitabilitas dan Biaya Operasional terhadap Pajak Penghasilan Badan Terhutang pada Perusahaan Pertambangan (Periode 2020-2022) - Yohana Magdalena; Agustiawan Agustiawan; R. Septian Armel (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research aims to determine the influence of capital structure, profitability and operational costs on Corporate Income Tax Payable at BEI companies for the 2020-2022 period. The population in this research are companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. The sample selection in this research used a purposive sampling technique. From the sample selection that was carried out, results were obtained from 21 companies that met the criteria. Data analysis uses quantitative descriptive methods using multiple regression models. The research results state that LDER has no influence on PPh Articles 25 & 29 of mining companies on the Indonesian Stock Exchange. ROA has an influence on PPh Articles 25 & 29 of mining companies on the Indonesian Stock Exchange. Meanwhile, operational costs have no influence on PPh Articles 25 & 29 of mining companies on the Indonesian Stock Exchange.